2017
DOI: 10.1002/jcp.25834
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor improves proliferation of endometrial epithelial cells by inhibition of endoplasmic reticulum stress during early pregnancy

Abstract: Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophin family binds to two transmembrane receptors; neurotrophic receptor tyrosine kinase 2 (NTRK2) with high affinity and p75 with low affinity. Although BDNF-NTRK2 signaling in the central nervous system is known, signaling in the female reproductive system is unknown. Therefore, we determined effects of BDNF on porcine endometrial luminal epithelial (pLE) cells isolated from Day 12 of pregnancy, as well as expression of BDNF and NTRK2 in endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…And, ER stress disrupts placentation and increases intrauterine growth restriction through regulating post‐translational processing of proteins (Yung et al, ). Furthermore, ER stress reduces proliferation of porcine endometrial cells through activation of UPR factors (Lim, Bae, Bazer, & Song, ). In accordance with previous reports, results of present study indicated that ER stress induced by tunicamycin, reduced proliferation of BEND cells which was reversed by FGF2.…”
Section: Discussionmentioning
confidence: 99%
“…And, ER stress disrupts placentation and increases intrauterine growth restriction through regulating post‐translational processing of proteins (Yung et al, ). Furthermore, ER stress reduces proliferation of porcine endometrial cells through activation of UPR factors (Lim, Bae, Bazer, & Song, ). In accordance with previous reports, results of present study indicated that ER stress induced by tunicamycin, reduced proliferation of BEND cells which was reversed by FGF2.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the porcine endometrium where its expression was located in epithelial cells, NTRK2 was mainly expressed here in stromal cells [57]. The expression of the NTRK2 gene, which encodes the receptor of brain derived neurotrophic factor, is conserved in mammalian uterus but its signalling function is not yet understood in the female reproductive system [58].…”
Section: Transcriptome Of the Three Endometrial Cell Typesmentioning
confidence: 84%
“…What's more, HOXA10 was regulated by many factors in EECs, including sex hormones (Taylor, Arici, Olive, & Igarashi, ; Wu et al., ; Zhong, Wang, & Liu, ), conceptus secretions (Blitek, Morawska, Kiewisz, & Ziecik, ) under normal physiological conditions. More importantly, variety of factors participated in the regulation of EECs under normal physiological conditions, including E2 (Shan, Li, Yang, & Li, ), P4 (Kyo et al., ), integrins (Park et al., ), periostin (Zheng et al., ), non‐esterified fatty acids (Chankeaw et al., ), growth factor (Islam, Yamagami, Yoshii, & Yamauchi, ), brain‐derived neurotrophic factor (Lim, Bae, Bazer, & Song, ). Moreover, HOXA10 was regulated by multiple miRNAs, such as miR‐135 in endometriosis (Petracco et al., ), miR‐494 in oral cancer (Libóriokimura, Jung, & Chan, ), miR‐218 in hepatocellular carcinoma cell (Zhong‐Di Xiao et al., ).…”
Section: Discussionmentioning
confidence: 99%